Ação do fluor na microdureza do esmalte humano submetido a dois tipos de agentes clareadores - Cunha, Lia Alves da [UNESP] (2005)
The aim of this study was to evaluate the ability of fluoride to induce remineralizatian of the human dental enamel subjected to nightguard vital bleaching and professional bleaching. Sixty teeth were divided into five groups: control; 10% peroxide carbamide; 10% peroxide carbamide and 0.05% fluoride; 35% hydrogen peroxide; 35% hydrogen peroxide and 0.05% fluoride. The Vickers microhardness of all specimens was measured before and after treatment. Complementary analysis comprised Atomic Absorption Spectrometry (AAE) and Scanning Electron Microscopy (SEM). Data were subjected to statistical analysis of variance (ANOVA), Dunnett's and Tukey's tests. The results revealed that there is significant reduction of enamel microhardness when subjected to the bleaching agents, compared to the control group. Carbamide peroxide promoted reduction of microhardness statistically bigger than hydrogen peroxide. The specimens that were exposed to fluoride showed a statistically significant smaller reduction of microhardness, compared with those not treated with fluoride. This difference was non-significant in teeth treated with carbamide peroxide and significant in teeth treated with hydrogen peroxide. Analysis by AAE .displayed that the groups not exposed to fluoride lost more calcium than their correspondents with remineralization. The SEM findings revealed morphologic changes in the enamel surface of bleached teeth, though these were not uniform through the entire surface. It was concluded that fluortherapy is an adequate method to minimize reduction of microhardness after nightguard or in-office vital bleaching